2015
DOI: 10.11607/ijp.4016
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Rehabilitation of Edentulism Prevents Malnutrition in Nursing Home Residents

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…(2) It is very important to monitor the periodontal status of the older patient and to provide a proper treatment plan, such as modification of general health-risk factors and oral health-specific risk factors, but professional hygiene or surgical procedures may also be necessary. (3) Prosthetic rehabilitation of the edentulous patient may help to prevent malnutrition [151] since it restores the chewing function. (4) In order to prevent problems related to the xerostomia and reduce exacerbation of carious lesions, it may be helpful to treat with saliva substitutes.…”
Section: Oral Managementmentioning
confidence: 99%
“…(2) It is very important to monitor the periodontal status of the older patient and to provide a proper treatment plan, such as modification of general health-risk factors and oral health-specific risk factors, but professional hygiene or surgical procedures may also be necessary. (3) Prosthetic rehabilitation of the edentulous patient may help to prevent malnutrition [151] since it restores the chewing function. (4) In order to prevent problems related to the xerostomia and reduce exacerbation of carious lesions, it may be helpful to treat with saliva substitutes.…”
Section: Oral Managementmentioning
confidence: 99%
“…Recently, a decrease in the number of present and functional teeth has been regarded as a risk factor for malnutrition that leads to high mortality in both community-dwelling older people and older people requiring nursing care [26][27][28][29][30][31]. In this study, root caries were more frequently observed in clasped teeth of RPD wearers.…”
Section: Discussionmentioning
confidence: 60%
“…3 This study is concurrent with the findings of similar studies demonstrating the association between prosthetic rehabilitation, nutrition and emotional wellbeing. [46][47][48][49][50][51] Also, the pandemic has worsened both the nutritional and emotional well-being of the geriatric individuals. The preventive measures that could be taken to improve dental and emotional health include professional counselling sessions in old age homes and regular dental screening camps and awareness camps to emphasize the importance of prosthetic rehabilitation in geriatric patients.…”
Section: Discussionmentioning
confidence: 99%